Comparative genomic profiling of CBFs pan-gene family in five yellowhorn cultivars and functional identification of Xg11_CBF11 - Wang, Juan; Liang, Xizhen; Zhang, Weiyang; Khalil, Asma; Wu, Yingying; Liu, Sisi; Tahir ul Qamar, Muhammad; Wang, Xingqiang; Guo, Jinping (Frontiers in Plant Science, 2024)
C-repeat binding factor (CBF) transcription factors can activate the expression of a series of cold regulation-related genes, thereby improving the cold resistance of plants. However, no detailed information is known about the biological functions of CBF proteins in yellowhorn (Xanthoceras sorbifolium). In this study, a total of 59 CBF gene family members were identified in five yellowhorn cultivars (WF18, Zhongshi 4, Jinguanxipei 2021, Zhong Guan NO.2, and XsoG11), revealing their intraspecific structural and functional diversity, with 8 core genes present in all cultivars. Phylogenetic and motif analyses highlighted conserved features and species-specific adaptations. Gene duplication events revealed that tandem duplicates are major factors involved in the expansion of this gene family in yellowhorn. Expression profiling under stress conditions demonstrated the involvement of these genes in stress responses. Of particular interest was Xg11_CBF11, which showed strong induction by low-temperature stress. Overexpression of Xg11_CBF11 in Arabidopsis thaliana was performed to validate its cold resistance function. The wild-type and T2 transgenic A. thaliana plants were subjected to low-temperature stress at 4℃ for 0, 24, and 48 h, and physiological indexes related to antioxidant enzyme activity, photosynthesis, and cell membrane permeability were determined by comparative test. The results were as follows: the POD and SOD activities of transgenic lines were significantly higher than those of wild-type lines, indicating Xg11_CBF11 improved the adaptability of A. thaliana to low-temperature; The increase of relative conductivity and malondialdehyde, the decrease of chlorophyll content in transgenic lines were smaller than those of wild-type lines, indicating Xg11_CBF11 enhanced the resistance of A. thaliana to low-temperature stress. These results implied that Xg11_CBF11 has a positive regulatory effect on A. thaliana 's response to low-temperature stress.